A Systematic Review of the Prevalence of Gestational Diabetes in Norway - Samira Behboudi-Gandevani (International Journal of Environmental Research and Public Health, 2021)
Gestational diabetes mellitus (GDM) is a major public health problem and a threat to maternal and child health. There is a lack of integrated and systematically synthesized knowledge about the prevalence GDM in Norway. Therefore, this systemic review aimed to present the best available peer-reviewed published evidence from the past 20 years about the prevalence of GDM in Norway. A comprehensive literature search was performed on online databases consisting of PubMed (including Medline), Web of Science, and Scopus to retrieve original research articles published on the prevalence of GDM up to August 2020. Also, databases of Norart and SveMed+ in the Norwegian language were searched to enhance the search coverage. Data were extracted using a standardized protocol and data collection form and were presented narratively. A total of 11 studies were selected to include for data analysis and synthesis with the total sample size of 2,314,191 pregnant women. The studies included heterogenous populations and mostly reported the prevalence of GDM in healthy mothers with singleton pregnancies. The prevalence of GDM in population registered-based studies in Norway was reported to be lower than 2%, using the World Health Organization (WHO) 1999 criteria. However, studies on high-risk populations such as the non-European ethnicity reported prevalence rates ranging from 8% to 15%. Given the evidence from available literature that reported trends in the prevalence of GDM, an increase in the prevalence of GDM across most racial/ethnic groups studied in Norway was observed. Overall, the prevalence of GDM in the low risk population of Norway is fairly low, but the available literature supports the perspective that the prevalence of GDM has shown an increasing trend in recent decades. This finding is very important for health service planning and evaluation, policy development, and research in Norway. Large-scale prospective studies, using the national data, are warranted to provide firm evidence over coming years. Our review findings can help policy makers devise appropriate strategies for improving women’s reproductive health.